P4.04 BARORECEPTOR SENSITIVITY IS REVERSED IN DIABETES AND IS UNAFFECTED BY ANTI-HYPERTENSIVE TREATMENT: A RODENT STUDY - Z. Kouchaki; E. Salum; J. Kals; P. Kampus; A.P. Avolio; M. Butlin (Artery Research, 2013)
Objectives: Diabetes is a complex disease associated with cardiovascular complications. This study compared baroreceptor sensitivity (BRS) in diabetic rats with and without anti-hypertensive treatment. Methods: Diabetes (induced by intraperitoneal injection of streptozotocin at 6 weeks of age) and control (saline injection) rats were divided into untreated (diabetic n=9, control n=5) and treated (diabetes+Tx n=9, control+Tx n=6) groups. Treatment groups received angiotensin II receptor antagonist, telmisartan (10 mg/kg/day, gavage). At 17 weeks of age, systolic pressure was measured by tail-cuff technique. The following week, rats were anaesthetised (urethane, 1.3 g/kg) and aortic pressure and heart rate measured during intravenous phenylephrine infusion (30 μg/kg/min). BRS was calculated by the slope of heart rate against mean pressure rise. Normal BRS was defined as a positive slope, and BRS dysfunction as a negative slope (Figure). Results: Both control (142±16 mmHg) and diabetic (132±22 mmHg) animals were hypertensive. Anti-hypertensive treatment successfully lowered systolic blood pressure (control+Tx 105±11 mmHg; diabetes+Tx 119±14 mmHg). BRS was typically positive in control (100%) and control+Tx (83%) rats. Conversely, BRS was impaired in both diabetic (33% positive) and diabetes+Tx (29% positive) rats. BRS impairment was significantly different between diabetic and control rats (p=0.007) and diabetes+Tx and control+Tx rats (p=0.002). However, there was no difference with anti-hypertensive treatment (diabetes, diabetes+Tx: p=0.42; control, contol+Tx: p=0.32). Conclusion: Baroreceptor sensitivity is impaired in diabetic rats and this is independent of the hypertensive state.